Unexpected Vascular Anomaly; Right Subclavian-Pulmonary Artery Connection Unraveled during Routine PDA Closer; Case Report (Razi Medical Journal, 2025)
Aberrant origin of the right subclavian artery (ARSA) is an extremely rare congenital vascular anomaly. A systemic connection to the pulmonary artery occurs due to abnormal embryogenesis of the aortic arch. The clinical presentation of the patient depends on the degree of shunt & associated cardiac problems, making most of the patients asymptomatic, or they complain of respiratory distress, differential cyanosis, and feeding difficulties. Echocardiography might suspect the problem, but computed tomography angiography and cardiac catheterization are essential for definitive diagnosis & for delineating the exact anatomy and hemodynamic significance. Early recognition is important to prevent complications such as pulmonary overcirculation, congestive heart failure, or vascular steal phenomena. Surgical or transcatheter correction is usually required to re-establish systemic arterial supply and disconnect the anomalous pulmonary connection. Reporting such rare cases adds to the understanding of vascular embryology and helps optimize diagnostic and therapeutic strategies
Keywords: Aberrant Right Subclavian Artery; Patent Ductus Arteriosus; Echocardiography; Angiographyز